2022
DOI: 10.1175/bams-d-21-0049.1
|View full text |Cite
|
Sign up to set email alerts
|

Measurements from inside a Thunderstorm Driven by Wildfire: The 2019 FIREX-AQ Field Experiment

Abstract: The 2019 Fire Influence on Regional to Global Environments and Air Quality (FIREX-AQ) field experiment obtained a diverse set of in-situ and remotely-sensed measurements before and during a pyrocumulonimbus (pyroCb) event over the Williams Flats fire in Washington State. This unique dataset confirms that pyroCb activity is an efficient vertical smoke transport pathway into the upper troposphere and lower stratosphere (UTLS). The magnitude of smoke plumes observed in the UTLS has increased significantly in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 81 publications
0
25
0
Order By: Relevance
“…1, purple curve), with a primary mode at 162 nm, a secondary mode at 228 nm, and a tail extending beyond 300 nm. More recently, we obtained direct sampling of a small-scale pyroCb in the troposphere at 8- to 9-km altitude within hours of emission from the August 2019 Williams Flats Fire in Washington, USA ( 34 ). CTs from that dataset (Fig.…”
Section: Fingerprints Of Pyrocb Persist In Ls Aerosol Microphysical P...mentioning
confidence: 99%
“…1, purple curve), with a primary mode at 162 nm, a secondary mode at 228 nm, and a tail extending beyond 300 nm. More recently, we obtained direct sampling of a small-scale pyroCb in the troposphere at 8- to 9-km altitude within hours of emission from the August 2019 Williams Flats Fire in Washington, USA ( 34 ). CTs from that dataset (Fig.…”
Section: Fingerprints Of Pyrocb Persist In Ls Aerosol Microphysical P...mentioning
confidence: 99%
“…This was due both to extensive cloud cover on 11 August (UTC, see Table S1 in Supporting Information S1 ) and to the low temperature fire being below detection for the GOES sensor even when cloud cover was limited for the remaining days MACH‐2 sampled this fire. This indicated that Nethker provided the smoldering end of the observed range in fire intensity with Williams Flats and its generation of towering pyrocumulonimbus clouds (Peterson et al., 2022 ) the most intense flaming end of the range, with the other fires in between. The ΔBC/ΔCO metric used to characterize the degree of flaming proposed by Selimovic et al.…”
Section: Resultsmentioning
confidence: 96%
“…For any given smoke plume there are four fundamental drivers causing the variability in the observations: (a) the fuels consumed, (b) the combustion phase (smoldering‐to‐flaming), (c) fire intensity and surface geometry, and (d) atmospheric processing as smoke travels away from the source. Fire intensity and the geometry of the surface burning (ranging from a large broad patch nearly as wide as it is long to a narrow fire front line along a burned perimeter) are critically important factors for vertical lofting and plume injection height, plume density (thick or thin) and geometry (spatial dimensions), and subsequent atmospheric processing that can differ from plume edges to plume core on the basis of light characteristics and locally variable oxidants across the plume spatial dimensions (e.g., Garofalo et al., 2019 ; Hodshire et al., 2019 ; Peterson et al., 2022 ; Wang et al., 2021 ). Additionally, meteorological conditions (e.g., Peterson et al., 2022 ) and the chemical composition of the background air (e.g., Hodshire et al., 2019 ) are important factors in atmospheric processing of the plume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategically building on this foundation will involve blending the knowledge base manifested in a pyroCbdetection climatology with wildfire data and penetrative data, such as operational and research cloud radar archives. It is also essential to continue the recent advancement in obtaining ground and airborne field measurements near and within active pyroCb activity 71,72 . Our new lens on the pyroCb danger, dynamics, and inherent coupling of biomass burning with the UTLS challenges scientists to uncover the historical imprint of pyroCbs to answer questions of where and when they develop and how they behave.…”
mentioning
confidence: 99%